Metode Weighted Product dalam Pemilihan Penerima Beasiswa Bagi Peserta Didik - Roni Roni; Sumijan Sumijan; Julius Santony (Ikatan Ahli Informatika Indonesia (IAII), 2019)
Scholarships are one of the factors that can increase learning motivation for students. This scholarship is one of the school programs to help parents of students to ease the burden of education costs of the students. In determining the scholarship recipients who meet the requirements and eligibility at the MA Raudlatul Ulum a decision support system is using the Weighted Product method. Decision making in the Weighted Product method is done by multiplication to connect the rating of each attribute, where the rating of each attribute must be raised by the weight of the attribute in question. In this study there are several criteria used in decision making, namely Average Value, Behavior, Extracurricular, Parent Income, and Dependents of Parents. The research carried out begins with determining the weight of each criterion, then the ranking process is carried out which will produce the most optimal alternative. Based on the results of testing that has been done, it can be concluded that the system is able to provide accuracy of 90% if compared with the results of testing manually.